Myocardial Enzyme Profile and Short-Term Prognosis of Patients with Prolonged Myocardial Damage after Transcatheter Aortic Valve Replacement - Han, Ke (Journal of Medical Biochemistry, 2025)
Abstract Background: This work investigated the changes in myocardial enzyme profile (MEP) and short-term prognosis (STP) in patients with myocardial damage (MD) after transcatheter aortic valve replacement (TAVR). Methods: 100 patients receiving TAVR surgery were selected and rolled into an observation group (Obs group, 50 cases) and a control group (Ctrl group, 50 cases) according to postoperative myocardial status. The changes in MEP before and after the TAVR and the STP within 3 days after surgery were compared and analyzed. Results: CK-MB levels were (21.6 ± 8.8) IU/L, (17.2 ± 7.1) IU/L, and (15.2 ± 6.4) IU/L at 12 h, 24 h, and 72 h after TAVR, respectively, in the Obs group; and the cTnT levels were (0.284 ± 0.13) ng/mL, (0.315 ± 0.15) ng/mL, and (0.363 ± 0.22) ng/mL, respectively, at the same time points. The CK-MB and cTnT levels in the Obs group were increased more obviously based on the conditions in the Ctrl group (P<0.05). After surgery, 23 cases of bleeding occurred in the Obs group, which was greatly more than 8 cases in the Ctrl group (P<0.05). Differences in ultrasonic test results was not obvious (P>0.05). Conclusion: The MEP of patients after TAVR generally increased, and the increase degree of patients with MD was more significant, which may be undertaken as an indicator to judge the postoperative MD. Patients with postoperative MD had a higher probability of postoperative bleeding.